2019
DOI: 10.1016/s2095-3119(18)61914-8
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of a homeodomain-leucine zipper gene HD-1 contributes to trichome initiation and development in cotton

Abstract: Plant trichomes originate from epidermal cells. In this work, we demonstrated that a homeodomain-leucine zipper gene, Gh_A06G1283 (GhHD-1A), was related to the leaf trichome trait in allotetraploid cotton and could be a candidate gene for the T 1 locus. The ortholog of GhHD-1A in the hairless accession Gossypium barbadense cv. Hai7124 was interrupted by a long terminal repeat (LTR) retrotransposon, while GhHD-1A worked well in the hairy accession G. hirsutum acc. T586. Sequence and phylogenetic analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Partial silencing of both homoeologs of HD-1 in tetraploid G. hirsutum resulted in a glabrous phenotype and delayed the timing of fibre initiation [15]. However, the hairless stem and leaf phenotype observed in G. barbadense is believed to be caused by a retrotransposon insertion in GbHD-1_At [17,18], making it nonfunctional, and GbHD-1_Dt might only be responsible for trichomes on the lower side of leaves and new buds [18]. In this study, we identified GaHD-1 as a potential candidate gene of the Ga_lintless locus responsible for both the glabrous and lintless phenotypes of the G. arboreum accession A2_106.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial silencing of both homoeologs of HD-1 in tetraploid G. hirsutum resulted in a glabrous phenotype and delayed the timing of fibre initiation [15]. However, the hairless stem and leaf phenotype observed in G. barbadense is believed to be caused by a retrotransposon insertion in GbHD-1_At [17,18], making it nonfunctional, and GbHD-1_Dt might only be responsible for trichomes on the lower side of leaves and new buds [18]. In this study, we identified GaHD-1 as a potential candidate gene of the Ga_lintless locus responsible for both the glabrous and lintless phenotypes of the G. arboreum accession A2_106.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in G. hirsutum has identified five major loci (T 1 -T 5 ) for the leaf/stem trichome trait [13]; among them, T 1 was located on chromosome A06 (Chr06) [14]. A homeodomain-leucine zipper gene HD-1 is thought to be the causative gene for T 1 [10,[15][16][17][18]. A long terminal repeat retrotransposon insertion in GbHD-1_At results in a lack of pubescence on the stem and leaf epidermis in G. barbadense [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar pattern of selection sweeps was observed in At sub-genome, where modern cultivars showed higher selection peaks than obsolete cultivars. The annotations represent FQ = Fibre quality [28][29][30][31][32], FY = Fibre yield [30], SBN = Sympodial branch node and EM = Early maturity [31,33,34]…”
Section: Differentiation and Domestication Between G Hirsutum Landramentioning
confidence: 99%
“…To further understand the genetic basis of these domestication sweeps, we mapped these selection sweeps with previously known QTLs. Some of the selection sweeps overlapped with previously reported QTL hotspots for multiple traits, i.e., for fiber quality (Liu, Zhang et al, 2016, Liu, Teng et al, 2017, Tang, Teng et al, 2015, Wang, Guo et al, 2006, Wang, Zhu et al, 2012, maturity (Ding, Ye et al, 2015, Niu, Cai et al, 2018, yield traits (Liu et al, 2017). Whole-genome duplication (polyploidy) provides the raw material for adaption (Hollister, 2015).…”
Section: Genetic Differentiation Between G Purpurascens and Cultivatmentioning
confidence: 84%